Status of Freshwater Crayfish Distribution in Thrace Region of Turkey - Guner, Utku; Harlioglu, Muzaffer Mustafa (Taylor & Francis Inc, 2010)
This review focuses on the present distribution of two crayfish species: narrow-clawed crayfish Astacus leptodactylus Eschscholtz and stone crayfish Austropotamobius torrentium (Schrank, 1803) in Thrace region of Turkey. The only known native (indigenous) freshwater crayfish species of Turkey is A. leptodactylus. It is found at more sites than A. torrentium. On the other hand, A. torrentium is only found in Thrace region of Turkey. The first population of A. torrentium was observed in Velika River in 1995. In 2006, the second population of A. torrentium was found in Madara Brook in the region, but the abundance of A. torrentium in Madara Brook was very low in comparison to Velika River. Moreover, further studies carried out in some water resources near the population of A. torrentium, such as Dev
Keywords: Astacus leptodactylus; Austropotamobius torrentium; crayfish; distribution; population; Thrace; Turkey